(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This research seeks to clarify the regulatory and educational role of the regulatory and educational institutions in reducing the phenomenon of financial and administrative corruption as a dangerous phenomenon of the communities, as it touched search kinds of financial and administrative corruption and the causes and effects, as well as to the role of educational institutions in reducing this phenomenon, and finally between experiments some SAIs and accounting Arab and foreign countries on how to reduce the phenomenon of financial and administrative corruption.The research aims to several targets which shed light on the role of educational and supervisory institutions in reducing corruption, a statement origins and evolution of and justification for financial and administrative concept of corruption and the reasons for his appearance and the most important manifestations of corruption and is already reflected on the particular national economy and on society in general.The research was presented a set of conclusions and recommendations that are consistent with the goals and accept its premises.